Drinking with Dickens - Dickens, Cedric (Rowman & Littlefield Publishers, 1998)
Drinking with Dickens is a light-hearted sketch by Cedric Dickens, the great-grandson of Charles Dickens. There are vivid and memorable drinking scenes in Dickens' books, and Drinking with Dickens abounds in recipes, many based on the drinks of Dickensian England and America: Bishop, Dog's Nose, Hot Bowl Punch, Milk Punch, Mint Julep, Sherry Cobbler, Shrub and Negus, to mention only a few. Unbelievably it seems to be the first book on this vast and important subject, and Cedric has added some recipes and experiences of his own. The Victorian sources include a penny notebook dated 1859 and kept by "Auntie Georgie," Georgina Hogarth, when she was looking after the younger children of Charles Dickens at Gads Hill. It starts with a recipe for Ginger Beer, a teetotal drink which calls for a quart of brandy! Then there is the catalogue for the sale of Gads Hill after Charles Dickens died which shows what was in the cellar at that time. This book transcends the generations. Cedric, with an eye for people and detail, describes a whole series of joyous episodes where drink, wisely taken, has been the catalyst.